2013
DOI: 10.1016/j.lmot.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Some factors modulating the strength of resurgence after extinction of an instrumental behavior

Abstract: In resurgence, an operant behavior that has undergone extinction can return (“resurge”) when a second operant that has replaced it itself undergoes extinction. The phenomenon may provide insight into relapse that may occur after incentive or contingency management therapies in humans. Three experiments with rats examined the impact of several variables on the strength of the resurgence effect. In each, pressing one lever (L1) was first reinforced and then extinguished while pressing a second, alternative, leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 34 publications
6
94
2
Order By: Relevance
“…4) in which groups that experienced lengthier extinction plus alternative reinforcement showed less resurgence than did a group that experienced only three sessions of extinction plus alternative reinforcement. On the other hand, a recent failure to replicate the findings of Leitenberg et al was reported by Winterbauer, Lucke, and Bouton (2013). This discrepancy will be addressed in the General Discussion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…4) in which groups that experienced lengthier extinction plus alternative reinforcement showed less resurgence than did a group that experienced only three sessions of extinction plus alternative reinforcement. On the other hand, a recent failure to replicate the findings of Leitenberg et al was reported by Winterbauer, Lucke, and Bouton (2013). This discrepancy will be addressed in the General Discussion.…”
Section: Discussionmentioning
confidence: 76%
“…Some recent data, however, are challenging for the effect of length of extinction on subsequent resurgence across groups. Winterbauer et al (2013, Exp. 2) compared groups that received four, 12, or 36 sessions of extinction plus alternative reinforcement and found no significant differences in subsequent resurgence.…”
Section: Discussionmentioning
confidence: 99%
“…Different groups received either consistent sucrose pellets or an unpredictable mixture of sucrose and grain pellets. If anything, the present sucrose pellets are weakly preferred to the present grain pellets (Bouton et al, 2013; Winterbauer, Lucke, & Bouton, 2013). As a result, any demonstration of increased responding for the mixture of grain and sucrose pellets over sucrose pellets alone would provide a compelling demonstration of the variety effect.…”
Section: Introductionmentioning
confidence: 82%
“…Although there is no record of the number of reinforcers contingent to each sequence in this phase, S1 with high probability, being the most frequent sequence, is likely to have received more reinforcers than S1 with low probability (the less frequent). This may have favored the reappearance of S1 in the Testing Phase (Winterbauer, Lucke & Bouton, 2013).…”
Section: Discussionmentioning
confidence: 99%